Open and distance learning: investigation on quality of experience among final year computer science students in UiTM Cawangan Pahang / Mohd Norafizal Abd Aziz ... [et al.] - Abd Aziz, Mohd Norafizal; Noradzan, Haslinda; Zakariah, Zazaleena; Ismail, Juhaida; Abdul Rahman, Rozeleenda (UiTM Press, 2022)
COVID-19 pandemic gave a big impact to all sectors in the world when it first hit at the end of 2019. The Education field is one of the worst affected sectors by the pandemic - having to experience major changes where all traditional face-to-face teaching and learning in classroom environments have changed to a fully online and distance approach. This new shift in approach had to be carried out to pursue the continuity of previous educational implementation in making the learning objectives achievable and concurrently preventing the spreading of the COVID-19 viruses. In UiTM, the first implementation of open and distance learning (ODL) in mid-March 2020 offered various perceptions from both students and lecturers as many factors needed to be considered to ensure the sessions meet the educational needs. Therefore, this study aims to investigate the quality of experience towards ODL among computer science students by assessing four major factors; learning materials provided by lecturers, online platforms being used, delivery methods and device capabilities during ODL. Using a quantitative methodology where responses from students were collected using a structured questionnaire, the analysed data then contributed new discoveries to this study. The analysis results reveal that the students rated their satisfactions towards the quality of experience during the implementation of ODL where the four factors discussed in this study were concerned, as 'good' and 'excellent'.